A comparative study of the corrosion of high copper dental amalgams - Acciari, H. A.; Codaro, E. N.; Guastaldi, Antonio Carlos [UNESP] (Elsevier B.V., 1998)
Metallographic studies carried out for Tytin-Plus and Dispersalloy amalgams show a porous multiphase material, whose surface phases are: gamma-(Ag3Sn), gamma(1)-(Ag2Hg3), eta'-(Cu6Sn5) and epsilon-(Cu3Sn). Additionally, Dispersalloy is present in the Ag-Cu eutectic. The application of surface analysis by SEM reveal a heterogeneous distribution of the above mentioned phases. Microstructures consisting of colonies or clusters were not observed. The corrosion testing of these materials was done in 0.9% NaCl aerated solution at 25 degrees C using potentiodynamic polarization curves and ac impedance measurements. The corrosion process in these multiphase systems can be interpreted as the sum of more than one electrodissolution process and the posterior formation of corrosion films. on each electrode, the corrosion film is formed by different mechanisms. (C) 1998 Elsevier B.V. B.V. All rights reserved.
Keywords: high copper amalgam; dental materials; biomaterials; chloride corrosion; electrochemical impedance spectroscopy (EIS)